Cuspal movement related to different polymerization protocols - Piccioni, Máyra Andressa Rodrigues Valinhos [UNESP]; Baratto-Filho, Flares; Kuga, Milton Carlos [UNESP]; Morais, Eduardo Christiano Caregnatto de; Campos, Edson Alves [UNESP] (Jaypee Brothers Medical Publishing, 2014)
Objective: The aim of this study to investigate the effects of different polymerization protocols on the cuspal movement in class II composite restorations. Materials and methods: Human premolar teeth were prepared with class II cavities and then restored with composite and three-step and two-step etch-and-rinse adhesive systems under different curing techniques (n = 10). It was used a lightemittingdiode curing unit and the mode of polymerization were: standard (exposure for 40 seconds at 700 mW/cm2), pulse-delay (initial exposure for 6 seconds at 350 mW/cm2 followed by a resting period of 3 minutes and a final exposure of 37 seconds at 700 mW/cm2) and soft-start curing (exposure 10 seconds at 350 mW/cm2 and 35 seconds at 700 mW/cm2). The cuspal distance (µm) was measured before and after the restorative procedure and the difference was recorded as cuspal movement. The data were submitted to two-way ANOVA and Bonferroni test (p < 0.05). Results: The type of adhesive system did not influenced the cuspal movement for all the curing methods. Standard protocol showed the highest values of cuspal movement and was statistically different from the pulse-delay and soft-start curing modes. Conclusion: Although the cuspal displacement was not completely avoided, alternative methods of photocuring should be considered to minimize the clinical consequences of composites contraction stress.
Keywords: Etch-and-rinse adhesive; Bonding technique; Polymerization; Cuspal movement